First successful frozen semen of the maned wolf (Chrysocyon brachyurus) - Teodoro, Laura O. [UNESP]; Camargo, Laiza S. [UNESP]; Scheeren, Verônica F. C. [UNESP]; Freitas-Dell'Aqua, Camila P. [UNESP]; Papa, Frederico O. [UNESP]; Honsho, Cristiane S.; Souza, Fabiana F. [UNESP] (Wiley, 2021)
This study aimed to describe successful cryopreservation of sperm from maned wolves (Chrysocyon brachyurus). Three ejaculates from 2 maned wolves were collected by digital manipulation of the penis and evaluated subjectively, centrifuged and frozen in BotuCrio® (Botupharma, Botucatu, Brazil) or Tris–yolk egg extender. Spermatozoa were thawed at 37ºC/30s or 70ºC/4s and evaluated for kinetics, morphology, plasma and acrosome membrane integrity, mitochondrial potential, hydrogen peroxide, superoxide anion and lipid peroxidation. From 5 thawed samples, two had sperm total motility >55% (56.0% and 64.0%) and progressive motility ~35% (35% and 40%), both frozen with Tris–yolk egg. Plasma and acrosome membrane integrity decreased and percentage of sperm defects increased post-thawing. We concluded that is possible to freeze spermatozoa from maned wolves using semen collection and processing methods applied for domestic dogs.
Keywords: captive-wolf; cryopreservation; spermatozoa